Concomitant cemento-osseous dysplasia and aneurysmal bone cyst of the mandible: a rare case report with literature review - Han-Gyeol Yeom; Jung-Hoon Yoon (BMC, 2020)
Abstract Background Concomitant cemento-osseous dysplasia (COD) and aneurysmal bone cyst (ABC) are rare in the head and neck region. In our search of the English language literature, we found only one case report describing the simultaneous occurrence of COD and ABC in the head and neck region. Here, we report a case of COD associated with ABC. Further, we performed a systematic search of the literature to identify studies on patients with COD associated with nonepithelial lined cysts of the jaws. Case presentation The patient was a 32-year-old woman who was referred from a private dental clinic because of a cystic lesion below the mandibular right first molar. She had no pain or significant systemic disease. After performing panoramic radiography and cone-beam computed tomography, the imaging diagnosis was COD with a cystic lesion, such as ABC or solitary bone cyst. Excisional biopsy was performed, which revealed concomitant COD and ABC. Conclusion This case of ABC associated with COD provides insight for the diagnostic process of radiographically mixed lesions with cystic changes.